Unbalanced Liquidity Management Evaluation of the Russian Banking Sector - Morozko, Nina; Morozko, Natalia; Didenko, Valentina (Journal of Reviews on Global Economics, 2018)
The monetary policy content both in the world and in Russia is changing. The past five years confirm that banking systems are experiencing unprecedented influence of both external and internal macroeconomic factors. Autonomous factors in the banking sector liquidity formation are factors that are not related to the Central Bank operations for its management. However, at present, there are no studies related to the study of the autonomous factors influence on the banking sector liquidity. This article presents a model that fills this gap. We use this model to answer a number of theoretical questions: how is the influence of autonomous factors on the banking sector liquidity carried out and in what stages of development are their manifestations stronger? The calculated model is able to test hypotheses that are informally discussed in political and academic circles. Based on the objectivity of the model, one can estimate the reliability of each of the hypotheses put forward in this study. For calculating the model, time series were used for each day for the period 2013-2016, taken at the site of the Central Bank of Russia. On the basis of the panel regressions device it is shown that among the autonomous factors of liquidity formation the largest impact on the Russian banking sector liquidity is made by the change in balances on the accounts of the enlarged government with the Bank of Russia. The conducted research will allow the Central Bank to forecast the banking sector demand in liquid funds, taking into account the autonomous factors influence.